Pattern of Utilization of Health Services among Tuberculosis Patients in Nkanu West Local Government Area of Enugu State - Ene , Catherine U.; Ugwuoke , Anthony C. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
Abstract The burden of the spread of tuberculosis (TB) in the world is high. In Nigeria, TB prevalence rate was as high as 546/100,000 population. As a result, TB control programme were mounted by governmental and nongovernmental agencies in the country and Nkanu West Local Government Area (LGA) using Directly Observed Treatment Short course (DOTS). However, behaviour change communication was necessary for the success of the programme which necessitated this research. Retrospective design was used to investigate the pattern of utilization of health services among TB patients in the DOTS health facilities in the Local Government Area over eleven yearperiod (2004-2014). A sample of 407 patients was studied. Their records were reviewed using a validated researcher’s self-developed TB Record Review Proforma (TbRReP). The data generated were analyzed descriptively. The resultant percentages, mode and means were used to answer the three research questions postulated to guide the study. Findings from the study showed that the mean increase in the prevalence rate of TB for the period was 6.17 per cent; the mean age of patients that utilized TB clinics was 36.67 years, and more male than female TB patients utilized the health services (male=56.27%: female=43.73). Based on the results, the researcher recommended among other things, mounting health education campaigns to sensitize TB patients in Nkanu West LGA on the need to utilize DOTS health services.